Perbandingan Regulasi Anti Strategic Lawsuit Against Public Participation (SLAPP) Lingkungan Hidup di Indonesia dan Filipina: Comparison of Environmental Anti- Strategic Lawsuit Against Public Participation (SLAPP) Regulations in Indonesia and the Philippines - Yudhitiya Dyah Sukmadewi (Hukum dan Masyarakat Madani, 2026)
Strategic Lawsuits Against Public Participation (SLAPP) in environmental cases remain a significant challenge to protecting the rights of individuals and communities advocating for ecological interests. Indonesia and the Philippines are ASEAN countries that adopted Anti-SLAPP regulations within a relatively similar period and share comparable characteristics as developing nations. Differences in their regulatory frameworks have created a need to examine the degree of legal certainty provided by each system. This study aims to compare Anti-SLAPP regulations in environmental litigation in Indonesia and the Philippines and to evaluate the legal certainty generated by their respective legal frameworks. The research employs a normative legal method with a comparative law approach. The analysis focuses on relevant regulations and judicial decisions using Jan Michiel Otto’s theory of legal certainty as the analytical framework. The findings indicate that Indonesia regulates Anti-SLAPP more specifically through a single environmental legal framework supported by implementing regulations and judicial procedural guidelines. This framework provides a clearer legal basis for protecting public participation from both civil and criminal lawsuits. In contrast, the Philippines regulates Anti-SLAPP through several legal instruments, resulting in a less comprehensive regulatory framework, although it provides a summary hearing mechanism to filter cases containing SLAPP elements. This study offers a comparative perspective on the legal certainty of Anti-SLAPP regulations in Indonesia and the Philippines as an effort to strengthen the protection of public participation in environmental law enforcement. Abstrak Litigasi strategis terhadap partisipasi publik (Strategic Lawsuit Against Public Participation atau Anti-SLAPP) dalam perkara lingkungan hidup masih menjadi tantangan dalam perlindungan hak masyarakat untuk memperjuangkan kepentingan ekologis. Indonesia dan Filipina merupakan negara ASEAN yang mengadopsi regulasi Anti-SLAPP dalam periode yang relatif berdekatan serta memiliki karakteristik serupa sebagai negara berkembang. Perbedaan pengaturan di kedua negara mendorong perlunya kajian mengenai tingkat kepastian hukum yang diberikan oleh masing-masing sistem. Penelitian ini bertujuan membandingkan pengaturan Anti-SLAPP dalam litigasi lingkungan di Indonesia dan Filipina serta mengevaluasi kepastian hukum yang dihasilkannya. Metode yang digunakan adalah penelitian hukum normatif dengan pendekatan perbandingan hukum. Analisis dilakukan terhadap regulasi dan putusan yang relevan dengan menggunakan teori kepastian hukum Jan Michiel Otto. Hasil penelitian menunjukkan bahwa Indonesia mengatur Anti-SLAPP secara lebih spesifik melalui satu kerangka regulasi lingkungan hidup yang didukung oleh peraturan pelaksana dan pedoman beracara di pengadilan. Pengaturan tersebut memberikan dasar hukum yang lebih jelas dalam melindungi partisipasi publik dari tuntutan perdata maupun pidana. Sebaliknya, Filipina mengatur Anti-SLAPP melalui beberapa regulasi sehingga pengaturannya tidak terkonsolidasi secara komprehensif, meskipun menyediakan mekanisme summary hearing untuk menyaring perkara yang mengandung unsur SLAPP. Penelitian ini memberikan perspektif komparatif mengenai tingkat kepastian hukum regulasi Anti-SLAPP di Indonesia dan Filipina sebagai upaya penguatan perlindungan partisipasi publik dalam penegakan hukum lingkungan.